2020
DOI: 10.1186/s12916-020-01815-3
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian and vegan diets and risks of total and site-specific fractures: results from the prospective EPIC-Oxford study

Abstract: Background There is limited prospective evidence on possible differences in fracture risks between vegetarians, vegans, and non-vegetarians. We aimed to study this in a prospective cohort with a large proportion of non-meat eaters. Methods In EPIC-Oxford, dietary information was collected at baseline (1993–2001) and at follow-up (≈ 2010). Participants were categorised into four diet groups at both time points (with 29,380 meat eaters, 8037 fish eaters, 15,499 vegetarians, and 1982 vegans at baseline in analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 53 publications
5
77
0
6
Order By: Relevance
“…Mean calcium intake was lowest in the vegan group with intermediate values in the vegetarian subgroup. Studies indicate that vegetarian, including vegan, adults have a lower bone mineral density [ 49 ] and a higher risk for fractures [ 50 ]. Two cross-sectional studies confirmed a lower bone mineral density among vegetarian and/or vegan children [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mean calcium intake was lowest in the vegan group with intermediate values in the vegetarian subgroup. Studies indicate that vegetarian, including vegan, adults have a lower bone mineral density [ 49 ] and a higher risk for fractures [ 50 ]. Two cross-sectional studies confirmed a lower bone mineral density among vegetarian and/or vegan children [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several short-term trials are already ongoing [ 161 ] with some raising concerns about changes in bone mineral density [ 65 ] when substituting meat with plant-based foods. A recent prospective study on the EPIC-Oxford cohort found that compared to meat eaters, hip fracture risk was higher in fish eaters, vegetarians and vegans—with vegans carrying the highest risks of total, hip, leg, and vertebral fractures [ 162 ]. This was likely due to lower BMI and lower intakes of calcium and protein, though further studies are needed.…”
Section: Gaps and Opportunitiesmentioning
confidence: 99%
“…Prospective epidemiological evidence suggests that individuals excluding some (e.g., fish-eaters and vegetarian) or all animal products (vegans) from their diets may have different risks of some major non-communicable diseases compared to meat-eaters. This includes lower risks of coronary heart disease [ 2 , 3 , 4 ], some cancers [ 5 , 6 , 7 , 8 ], and diabetes [ 9 , 10 ] but possibly an increased risk of stroke [ 4 ] and fractures [ 11 ], in some or all of the non-meat-eating diet groups. Metabolomics has the potential to reveal underlying mechanisms in such diet-disease relationships [ 12 ], because metabolite concentrations reflect dietary, lifestyle, environmental and genetic factors as well as disease states [ 13 ].…”
Section: Introductionmentioning
confidence: 99%